Kolaborasi Model Pentahelix dalam Percepatan Penurunan Stunting di Kabupaten Jombang - Arsyi Ananda Putri; Diana Hertati (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Stunting is a national problem that is still a concern because it relates to the nutritional condition of toddlers as the nation's next generation. The Jombang Regency Government launched the Pentahelix collaboration involving five elements: academia, business, communities, government, and media, to reduce stunting rates. This study aims to identify, describe, and analyze the collaboration of the Penta helix model in accelerating the reduction of stunting in Jombang Regency. The type of research used in this research is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The data analysis technique consists of four analysis components: data collection, data condensation, data presentation, and drawing conclusions or verification. Based on the research results, the five Pentahelix elements contribute according to their respective functions. Implementing the Pentahelix collaboration program has proven to reduce annual stunting rates by up to 8.43% consistently.